Fourier transform infrared and near-infrared spectroscopic methods for the detection of toxic Diethylene Glycol (DEG) contaminant in glycerin based cough syrup. Issue 6 (2010) - Ahmed Ahmed, M. Khalique M. Khalique; McLeod McLeod, Michael P. Michael P.; Nézivar Nézivar, Jean Jean; Giuliani Giuliani, Allison W. Allison W.
Abstract : Recently there have been reports of the contamination of cough syrups with Diethylene Glycol (DEG). The consumption of such cough syrups has devastating effects on the health. In this paper we report evidence that Fourier transform infrared (FT-IR) and near-infrared (NIR) spectroscopic techniques are viable, simple, cost effective, rapid and fool proof methods for the identification and quantification of DEG in glycerin based cough syrups. The FT-IR and NIR spectra of the glycerin based cough syrup and up to 50:50 mixtures of DEG in cough syrup are recorded. The major peaks in the FT-IR spectrum of the cough syrup are assigned to the OH stretching (∼3300 cm −1 ), CH stretching (∼2900 cm −1 ), CH bending (1500–1200 cm −1 ) and C–O stretching (1200–900 cm −1 ) vibrational modes. In the FT-IR spectra of the mixtures, DEG contribute distinct peaks due to the vibrations of the C–O (920 cm −1 ) and OC2 H4 (892 cm −1 ) moieties of its backbone and form the basis of the DEG detection and quantification. The prominent peaks of the NIR spectra of cough syrup and DEG are assigned to the first overtones of OH and CH, and to the combination of OH and CH fundamental vibrations. Both FT-IR and NIR Partial Least Square (PLS) calibrations produced correlation coefficients of 0.98.